1981
DOI: 10.1111/1523-1747.ep12525463
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Xeroradiographic and Ultrasound Detection of Corticosteroid Induced Dermal Thinning

Abstract: A pulsed ultrasound technique was shown to have a high degree of correlation with the established xeroradiographic method for the determination of dermal thickness both in normal skin and corticosteroid treated skin, although xeroradiography consistently gave a higher value than ultrasound. Using the pulsed ultrasound technique, an early onset of dermal thinning could be detected 2 days following treatment with creams containing 0.05% clobetasol propionate and 0.1% beta-methasone 17-valerate. The amount of der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 9 publications
2
28
0
1
Order By: Relevance
“…The methodology has originally been developed by Marks. 49 These two methods delineate one thickness of skin as well as they allow the selective measuring of epidermal or dermal thickness without any other tissues. All of these methods are capable of detecting skin atrophy induced by a potent topical GC.…”
Section: 34mentioning
confidence: 99%
“…The methodology has originally been developed by Marks. 49 These two methods delineate one thickness of skin as well as they allow the selective measuring of epidermal or dermal thickness without any other tissues. All of these methods are capable of detecting skin atrophy induced by a potent topical GC.…”
Section: 34mentioning
confidence: 99%
“…Skin Pharmacol Appl Skin Physiol 2002; 15:71-84 Unholzer /Korting Tan et al [3,4] confirmed the good correlation between both methods and demonstrated the high reproducibility of sonographic measurement. In their hands, ultrasound consistently gave a smaller value of skin thickness than xeroradiography did [3,4].…”
mentioning
confidence: 86%
“…Tan et al [3], using a 15-MHz A-scan device, were the first to prove that application of betamethasone 17-valerate 0.1% cream and clobetasol 17-propionate 0.05% cream for 6 weeks reduces the total thickness of normal skin by 16 and 22%, respectively. Even dermal thinning of 5 and 4%, respectively, after 2 days of treatment could be detected by means of ultrasound [3].…”
Section: Cutaneous 20-mhz Sonography For the Assessment Of Unwanted Dmentioning
confidence: 99%
See 2 more Smart Citations